Employees' Communication Patterns in Unorganized Idea-sharing Activities - Vrgovic, Petar; Vidicki, Predrag; Senk, Vojin (International Journal of Industrial Engineering and Management, 2013)
Idea management is frequently observed as the front end of innovation process. Before idea management is implemented in an organization, it may be significant to research what are intuitive and spontaneous patterns of behavior expressed by the potential idea sharers. This research focuseson spontaneous idea sharing behaviors of employees in Serbian industrial companies, focusing on those behaviorsthat were not systematically and proactively organizedby their companies. The goal of this research was to explore the frequency of idea sharing behaviors of employees and the idea-sharing and communication patterns that they express, the type of verbal stimulus relevant to their idea communication activities, and feedback stimuli that ideators experience.Findings suggest that there is significantcreative potential that is notused, explaining the suboptimal usage of employeescreative input with bad practices by the management. Article history: Received (2 November 2012); Revised (8 December 2012); Accepted (16 January 2013)